Exposição à progesterona prévia à IATF não interfere na qualidade oocitária e expressão gênica de células do cumulus de vacas Bos indicus em anestro - Santos, Ana Paula Castro (2021)
Currently, Time Artificial Insemination (TAI) is well established as a biotech applied in reproductive programs. TAI protocols were developed to promote the control of luteal and follicular functions, which results in synchronization rates of approximately 85%, being lower in animals with a low body condition score. The success of TAI is due, in part, to the stimulation of exogenous progesterone in the pulsatility of GnRH and LH, which allows the ovulation of a preovulatory follicle in the beginning of the postpartum period. Higher pregnancy rates have been found in recent postpartum Zebu cows treated with injectable progesterone prior to TAI protocol. Progesterone acts in the most sensitive areas of the hypothalamic-pituitary axis in the GnRH and LH release, favors the expansion and decreases the apoptosis of cumulus cells, however, it is still unknown why this increase in the pregnancy rate of previously treated animals with this hormone. In the current study, Bos indicus cows (N=30) were treated with 150 mg of injectable progesterone ten days before (D-10) the ovulation synchronization protocol (D0), based on intravaginal progesterone implant and estradiol benzoate. After five days (D5), all visible follicles were aspirated. COCs were selected, classified and oocytes stored in liquid nitrogen for subsequent real-time PCR analysis, as well as cumulus cells. In PCR, oocyte quality (BMP15 and GDF9), cumulus cell expansion (HAS2) and apoptosis control (BAX and BCL2) genes were analyzed. There was no significant difference in oocyte quality and relative expression of the transcripts evaluated, demonstrating that injectable progesterone does not interfere in the quality of oocytes and in the control of apoptosis and expansion of cumulus cells, which is not the cause of increased pregnancy in treated animals with this hormone.